Discrete cytosolic macromolecular BRAF complexes exhibit distinct activities and composition. (16th January 2017) - Diedrich, Britta; Rigbolt, Kristoffer TG; Röring, Michael; Herr, Ricarda; Kaeser‐Pebernard, Stephanie; Gretzmeier, Christine; Murphy, Robert F; Brummer, Tilman; Dengjel, Jörn
Abstract: As a central element within the RAS/ERK pathway, the serine/threonine kinase BRAF plays a key role in development and homeostasis and represents the most frequently mutated kinase in tumors. Consequently, it has emerged as an important therapeutic target in various malignancies. Nevertheless, the BRAF activation cycle still raises many mechanistic questions as illustrated by the paradoxical action and side effects of RAF inhibitors. By applying SEC‐PCP‐SILAC, we analyzed protein–protein interactions of hyperactive BRAF V 600E and wild‐type BRAF (BRAF WT ). We identified two macromolecular, cytosolic BRAF complexes of distinct molecular composition and phosphorylation status. Hyperactive BRAF V 600E resides in large complexes of higher molecular mass and activity, while BRAF WT is confined to smaller, slightly less active complexes. However, expression of oncogenic K‐Ras G12V, either by itself or in combination with RAF dimer promoting inhibitors, induces the incorporation of BRAF WT into large, active complexes, whereas pharmacological inhibition of BRAF V 600E has the opposite effect. Thus, the quaternary structure of BRAF complexes is shaped by its activation status, the conformation of its kinase domain, and clinically relevant inhibitors. Synopsis: The serine/threonine kinase BRAF plays a key role in development and homeostasis and represents the most frequently mutated kinase in tumors. We characterize two macromolecular, cytosolic BRAF complexes of distinct molecular composition and phosphorylation status. BRAF resides minimally in two distinct macromolecular cytosolic protein complexes. Active BRAF forms larger complexes characterized by the presence of HSP90/CDC37. Less active BRAF resides in smaller complexes characterized by 14‐3‐3 proteins. Clinically relevant kinase inhibitors alter BRAF complex compositions depending on the expressed BRAF mutant. Abstract : Proteomics‐based identification of distinct molecular interactions and modifications of wild‐type and melanoma‐associated mutant BRAF reveals the effects of BRAF activators and inhibitors on the quaternary structure of this major therapeutic target.